SELF-ACTUALIZATION IN NABILA’S CHARACTER IN THE NOVEL RIHLAH ILALLAH BY NAJIB AL-KILANI: LITERARY PSYCHOLOGY ANALYSIS - Auliya Hizbullah; Uki Sukiman (Afshaha: Jurnal Bahasa dan Sastra Arab, 2025)
Nabila’s character undergoes various emotional and spiritual journeys that reflect her efforts to achieve self-actualization. However, this process does not occur instantly. Multiple factors influence Nabila’s character development, including her life experiences, social environment, personal challenges, and the values she holds. This study aims to describe the hierarchy of needs achieved by Nabila and the characteristics of her self-actualization in Najib Al-Kilani’s novel Rihlah Ilallah, using Abraham Maslow’s literary psychological perspective. Maslow’s theory emphasizes individual freedom in expressing opinions and making life choices, while also highlighting the importance of humanity’s relationship with the surrounding environment. According to Maslow, individuals reach true happiness when they attain the level of self-actualization. His humanistic theory, known as the Hierarchy of Needs, outlines human motivation as a progression through structured stages. This research employs a descriptive qualitative method, drawing data from the novel Rihlah Ilallah and several relevant supporting studies. The results indicate that Nabila’s character fulfills all five levels of basic needs: physiological needs, safety needs, love and belonging, esteem, and self-actualization. Additionally, she displays the key traits of a self-actualized individual, including efficient perception of reality, problem-centeredness, high creativity, concern for the welfare of others, and a need for privacy.